PENGARUH PUPUK ALAMI BERMIKROBA (BIO-NATURAL FERTILIZER) TERHADAP SERAPAN FOSFOR DAN PERTUMBUHAN KACANG TANAH PADA TANAH ALFISOL, ENTISOL, DAN VERTISOL - Yasinta Choirina; Sudadi Sudadi; Hery Widijanto (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Effect of Bio-Natural Fertilizer on Phosphorus Uptake and Growth of Peanut in Alfisols, Entisols, and Vertisols. Development of bio-natural fertilizer was needed to overcome the scarcity of fertilizer in Indonesia, the deficiency of soil nutrient, and low efficiency of fertilizer use. The research purposed to study the effect of bio-natural fertilizer formula and find out of best formula on P uptake and growth of peanuts in various soils ordo. The experiment used a completely randomized design with three factors. The first factor was bio-natural fertilizer P1 (vermicompost 100% without enrichment material, without microbial inoculums), P2 (vermicompost 66,67%, enrichment material 33,33% and microbial inoculum of NPKS with proportion of 2:2:1:1), and P3 (vermicompost 33,33%, enrichment material 66,67% and microbial inoculum of NPKS with proportion of 2:2:1:1). The second factor was peanut varieties, Elephant and Rabbit varieties. The third factor was soil ordo, Alfisols, Entisols, and Vertisols. The variables observed were av-P, P uptake, shoot dry weight, soil pH, population of P-solubilizing fungi, plant height, and shoot fresh weight. Data was analyzed by F test at 95% level confidence. The results showed that formula of bio-natural fertilizer influence significantly on P uptake and growth of peanuts in various soils. The formula of bio-natural fertilizer P2 is the best formula to increased P uptake of peanut on Alfisols, Entisol, and Vertisol, as well as for highest peanut growth on Alfisols.